Synthesis of 5,5-Disubstituted Butenolides Based on a Pd-Catalyzed ©-Arylation Strategy - Hyde, Alan M. (2009)
[Image: see text] Methods for the construction of quaternary carbon centers are of great interest to synthetic chemists due to their presence in natural products. Development of the Pd-catalyzed arylation of butenolides with high selectivity for the γ-position, allows for a facile construction of quaternary centers. The preparation of a wide variety of γ-aryl butenolides containing a number of functional groups is outlined. An application of this chemistry for a one-pot synthesis of a tricyclic tetrahydroisoquinolinone is demonstrated.